1999
DOI: 10.1021/la980899m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipid with Covalently Attached Poly(ethylene glycol) on the Surface Properties of Liposomal Bilayer Membranes

Abstract: The effect of lipid with covalently attached poly(ethylene glycol) (PEG−lipid) on the surface properties of liposomal bilayer membranes was examined from standpoints of particle size, surface potential, microviscosity, micropolarity, and permeability. The particle size and the absolute value of the ζ potential of liposomes decreased with increasing mole fraction of PEG−lipid. The permeability of PEG−liposomes was decreased as compared with regular liposomes. The microviscosity and the micropolarity of liposoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…A high colloidal stability of the suspensions was further imparted by selecting anionic phospholipids (DMPG and DSPE-PEG) so that strong interparticle electrostatic repulsions were generated. The somewhat lowerpotential values observed for the PEGylated lipid structures, which are in agreement with the data of Piperoudi et al [15] and Yoshida et al [16], can be rationalized by assuming that the slipping plane at the PEG-aqueous layer interface is moved further from the vesicle or ML surface.…”
Section: Discussionsupporting
confidence: 88%
“…A high colloidal stability of the suspensions was further imparted by selecting anionic phospholipids (DMPG and DSPE-PEG) so that strong interparticle electrostatic repulsions were generated. The somewhat lowerpotential values observed for the PEGylated lipid structures, which are in agreement with the data of Piperoudi et al [15] and Yoshida et al [16], can be rationalized by assuming that the slipping plane at the PEG-aqueous layer interface is moved further from the vesicle or ML surface.…”
Section: Discussionsupporting
confidence: 88%
“…The higher the molar mass of PEG (i.e., the longer the PEG chain), the lower was the surface charge of the vesicles. This can be explained in terms of shielding of the negatively charged vesicle surface by the exposed PEG chains, which decreased the zeta potential of the vesicle [29,30]. However, the zeta potential of the POPC/DMPEG3000 aggregates was about 213 mV, which shows that the shorter C14 chains of the DMPEG-lipid clearly affect the packing of the lipids in the liposome.…”
Section: Zeta Potentials Of the Pegylated Aggregatesmentioning
confidence: 99%
“…1 [19]. Extrusion, a more recently developed method of forming lipid vesicles, has become a widely accepted technique due to the ability to control vesicle size [19,20]. …”
Section: Liposome Characterizationmentioning
confidence: 99%
“…Additionally, they performed Monte-Carlo simulations which suggested that a large portion of the liposome surface was uncovered by PEG-2000 polymers at 2-10% addition of PEG modified lipid (molar basis). Yoshida et al also conducted simulations to estimate surface coverage and concluded that approximately 45% of the surface would be covered at 5% addition of PEG-2000 [20]. As far as the conformation of the PEG chains is concerned, Moghimi and Szebeni suggest that at very low coverages (below 5%), the polymers exhibit a mushroom-like behavior with a lack of extension into the aqueous bulk phase [27].…”
Section: Liposomes Incorporated With Polyethylene Glycol (Peg)mentioning
confidence: 99%